2019
DOI: 10.1002/cjoc.201800549
|View full text |Cite
|
Sign up to set email alerts
|

Computational I(III)—X BDEs for Benziodoxol(on)e‐based Hypervalent Iodine Reagents: Implications for Their Functional Group Transfer Abilities

Abstract: Summary of main observation and conclusion The first comprehensive I(III)―X (X = F, Br, CN, N3, CF3, etc.) bond dissociation energy (BDE) scales for benziodoxol(on)e‐based hypervalent iodine reagents have been developed by virtue of DFT calculations. Excellent correlation is observed between the I(III)―X BDEs and the X―H BDEs, offering a powerful avenue to quickly estimate the group‐transfer ability of a novel benziodoxol(on)e‐based hypervalent reagent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 64 publications
(5 reference statements)
1
27
0
Order By: Relevance
“…It is remarkable that despite the higher IÀ CN bond dissociation energy compared to IÀ N 3 bond in ABX, these reactions have a similar outcome. [13] The 1-electron process reported for iron herein differs also with the 2-electron oxidative processes reported for the reaction of a variety of λ 3 -iodanes with 4d and 5d transition metal complexes (Pd, Rh, Ir, Au), [14] as well as with late 3d transition metals, such as Cu and Ni. [15] The N 3 N' ligand stabilizes the electrophilic Fe IV cyanide complex, [(N 3 N')Fe IV (CN)] ( 4) as reported by the Schrock group.…”
Section: Resultsmentioning
confidence: 46%
“…It is remarkable that despite the higher IÀ CN bond dissociation energy compared to IÀ N 3 bond in ABX, these reactions have a similar outcome. [13] The 1-electron process reported for iron herein differs also with the 2-electron oxidative processes reported for the reaction of a variety of λ 3 -iodanes with 4d and 5d transition metal complexes (Pd, Rh, Ir, Au), [14] as well as with late 3d transition metals, such as Cu and Ni. [15] The N 3 N' ligand stabilizes the electrophilic Fe IV cyanide complex, [(N 3 N')Fe IV (CN)] ( 4) as reported by the Schrock group.…”
Section: Resultsmentioning
confidence: 46%
“…Xue and Yang and co‐workers studied the bond dissociation energy (BDE) of the exocyclic ligand of benziodoxol(on)e‐based hypervalent iodine reagents using DFT [109] . They found that meta and para substituents had a small influence on the BDE, while ortho substituents could significantly decrease the BDE by means of steric hindrance.…”
Section: Computational Insightsmentioning
confidence: 99%
“…Heterolytic or homolytic cleavage of a weak, threecenter four-electron (3c-4e) bond of HVI progresses the chemical reaction. Therefore, the BDE of the 3c-4e bond of HVI is an essential parameter that has been calculated by the DFT method on demand [16][17][18][19] . We previously reported the BDE value of 3c-4e bonds in various HVIs on the basis of DFT calculations 19 .…”
Section: Machine Learning Enabling Prediction Of the Bond Dissociation Enthalpy Of Hypervalent Iodine From Smilesmentioning
confidence: 99%